PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) DENGAN PENDEKATAN ILMIAH (SCIENTIFIC APPROACH) PADA MATERI SEGITIGA KELAS VII SMP SE-KABUPATEN KARANGANYAR TAHUN PELAJARAN 2013/2014 - Titik Yuniarti; Riyadi Riyadi; Sri Subanti (Jurnal Pembelajaran Matematika, 2014)
Absrtact: The aims of this research were: (1) to describe the Problem Based Learning process with using of the valid and practical scientific approach to the main subject of triangle for the VII degree of junior high school, (2) to describe the effectiveness of Problem Based Learning tools by using scientific approach which had been developed. This research run in two phases. The first phase was the process of the development of learning tools used 4-D model. This model consisted of four phases namely, (1) defined phase, (2) designed phase, (3) developed phase, and (4) disseminated phase. The second phase was the test of the effectiveness of the learning tools that has been developed using experiment method. The population was the students of the VII degree of Tasikmadu junior high school. The sampling was conducted randomly, the one was as the experiment class and the other was as control class. The results of this research were as follows. (1) The development of the learning tools conducted was valid and practical because the equipment that was developed based on the strong rational theory, it had internal consistency, and the learning equipment implicated in the learning process, (2) This learning used Problem Based Learning process with the scientific approach was better than the direct learning. Keywords: Development of learning, problem based learning, scientific approach